Factors influencing retention among hospital nurses: systematic review. (11th March 2021) - Marufu, Takawira C; Collins, Alexandra; Vargas, Liavel; Gillespie, Lucy; Almghairbi, Dalal
Abstract : Background: Recruitment and retention of nursing staff is the biggest workforce challenge faced by healthcare institutions. Across the UK, there are currently around 50 000 nursing vacancies, and the number of people leaving the Nursing and Midwifery Council register is increasing. Objective: This review comprehensively compiled an update on factors affecting retention among hospital nursing staff. Methods: Five online databases; EMBASE, MEDLINE, SCOPUS, CINAHL and NICE Evidence were searched for relevant primary studies published until 31 December 2018 on retention among nurses in hospitals. Results: Forty-seven studies met the inclusion criteria. Nine domains influencing staff turnover were found: nursing leadership and management, education and career advancement, organisational (work) environment, staffing levels, professional issues, support at work, personal influences, demographic influences, and financial remuneration. Conclusion: Identified turnover factors are long-standing. To mitigate the impact of these factors, evaluation of current workforce strategies should be high priority.